THE ARABIC COGNATES OR ORIGINS OF PLURAL MARKERS IN WORLD LANGUAGES: A RADICAL LINGUISTIC THEORY APPROACH - Zaidan Ali Jassem (Indonesian EFL Journal, 2015)
This paper traces the Arabic origins of "plural markers" in world languages from a radical linguistic (or lexical root) theory perspective. The data comprises the main plural markers like cats/oxen in 60 world languages from 14 major and minor families- viz., Indo-European, Sino-Tibetan, Afro-Asiatic, Austronesian, Dravidian, Turkic, Mayan, Altaic (Japonic), Niger-Congo, Bantu, Uto-Aztec, Tai-Kadai, Uralic, and Basque, which constitute 60% of world languages and whose speakers make up 96% of world population. The results clearly show that plural markers, which are limited to a few markers in all languages comprised of â€“s/-as/-at, -en, -im, -a/-e/-i/-o/-u, and Ã˜, have true Arabic cognates with the same or similar forms and meanings, whose differences are due to natural and plausible causes and different routes of linguistic change. Therefore, the results reject the traditional classification of the Comparative Method and/or Family Tree Model of such languages into separate, unrelated families, supporting instead the adequacy of the radical linguistic theory according to which all world languages are related to one another, which eventually stemmed from a radical or root language which has been preserved almost intact in Arabic as the most conservative and productive language. In fact, Arabic can be safely said to be the radical language itself for, besides other linguistic features, sharing the plural cognates in this case with all the other languages alone.Keywords: Plurality, language families and relationships, radical world language, radical linguistic theory